PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS FLASH PADA PEMBELAJARAN MATEMATIKA - Fitra Hayati; M. Jainuri; Hidayati Rais (Pendidikan Matematika | STKIP YM Bangko, 2021)
The purpose of this research to develop multimedia learning interactive used Adobe Flash CS3 Professional of learning math class VII SMP/MTs valid, practical, and effective. This research was used research and development method by APPED model. Multimedia learning interactive that validity by five people experts. The validity was seen from the sheets validation, practility from the sheets inquiries response students and interviews students, while effectiveness from the result of lear and activities learn students. The results of this research showing the scores an average of the validation by experts math 4,22 with the category very valid, the indonesian 3,88 with the category very valid, the media 4,78 with the category very valid, and validation teacher math 4,80 with the category very valid. The validation overall 4,58 with the category very valid. Acquisition presentase response students of 82,27% with the category of practical. Presentase the results of learning classical of 77,3% with the category of effective and average presentase students activities of 68,64% with the category of active. Based on the results of research and development, multimedia learning interactive has valid, practical, and effective